Mesenchymal Stem Cells From a Hypoxic Culture Can Improve Rotator Cuff Tear Repair. (April 2022) - Chen, Hsin-Shui; Yau, Yun-Chain; Ko, Pin-Tsou; Yen, Betty Lin-Ju; Ho, Chun-Te; Hung, Shih-Chieh
A rotator cuff tear is an age-related common cause of pain and disability. Studies including our previously published ones have demonstrated that mesenchymal stem cells cultured under hypoxic conditions [hypoxic multipotent stromal cells (MSCs)] facilitate the retention of transplanted cells and promote wound healing. However, there are very few, if any, reports targeting the punctured supraspinatus tendons to create more or equally serous wounds as age-related tears of rotator cuff. It remains to be determined whether transplantation of bone-marrow-derived hypoxic MSCs into the punctured supraspinatus tendon improves tendon repair and, when combined with ultrasound-guided delivery, could be used for future clinical applications. In this study, we used a total of 33 Sprague-Dawley rats in different groups for normal no-punched control, hypoxic MSC treatment, nontreated vehicle control, and MSC preparation, and then evaluated treatment outcomes by biomechanical testing and histological analysis. We found that the ultimate failure load of the hypoxic MSC-treated group was close to that of the normal tendon and significantly greater than that of the nontreated vehicle control group. In vivo tracking of cells labeled with superparamagnetic iron oxide (SPIO) nanoparticles revealed an enhanced retention of transplanted cells at the tear site. Our study demonstrates that hypoxic MSCs improve rotator cuff tear repair in a rat model.